PROBLEMATIKA PENERAPAN KURIKULUM 2013: STUDI KASUS DI KABUPATEN MANGGARAI NUSA TENGGARA TIMUR - Yohanes Wendelinus Dasor (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
The 2013 curriculum was born as an answer to the weaknesses and shortcomings of the 2006 KTSP curriculum which is directed to prepare students to have the ability to live as individuals and citizens who are faithful, productive, creative, innovative, and affective and able to contribute to the life of society, nation, state, and world civilization. And the purpose of this study is to determine the problems of implementing the 2013 curriculum in Manggarai region, NTT. This research is a type of qualitative research conducted at educational institutions from elementary to high school levels in Manggarai region, NTT. The data collection techniques used were interviews, observation and documentary studies. The data analysis technique refers to the data analysis model used by B. Mathew Miles and A. Michael Huberman consisting of three activities, namely; data reduction, data presentation, and conclusion / verification. The results showed that there were several opportunities for the implementation of the 2013 curriculum in Manggarai region, NTT, namely the thematic-integrative approach, the scientific approach and authentic assessment. While the challenges are a thematic approach based on local culture, challenges in making lesson plans, challenges in implementing learning and challenges in making assessments.